IMPLEMENTASI MODEL PROBLEM BASED LEARNING (PBL) DALAM MENINGKATKAN KEMAMPUAN BERBICARA SISWA KELAS 8 SMPN 7 MATARAM - Suherni, Suherni (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
Speaking Ability improvement with Problem Based Learning (PBL) of students of SMPN 7 Mataram grade VII. This is Class Action Research with 31 students of 8th grade as the subject. Data collecting through observation and speaking test. Data analysis is statistical descriptive quantitative. The result of the research proved that speaking ability through Problem Based Learning (PBL) in phase I was 58% and phase II was 74%. Students’ learning activity in phase I was 83% with very good cathegory and students’ learning activity in phase II was 93% with very good cathegory. This showed that Problem Based Learning (PBL) able to improve students’ speaking ability of SMPN 7 Mataram 8th grade